Pengaruh konsentrasi kalium nitrat (KNO3) terhadap pertumbuhan dan hasil bunga tanaman Krisan pot (Crysanthemum morifolium) varietas Cyra Agrihorti - Ano Zeim; Edy Sofyadi; Aghnia Rahmawati; Rini Sitawati (University of Insan Cendekia Mandiri, 2022)
Potted chrysanthemum plants are very popular with the public because of their various colors, sizes and shapes. The experiment was aimed to give the concentration of potassium nitrate (KNO3) which had a good effect on the growth and yield of potted chrysanthemums cyra agrihorti varieties. The experiment was carried out from March to May 2021 in Cimeta Village, Tugumukti Village, Cisarua District, West Bandung Regency at an altitude of 1312 m above sea level. The experiment method used complete randomized design (CRDB) of six treatments and four replications. The KNO3 concentration treatments used were A = 0 g/liter, B = 1 g/liter, C = 2 g/liter, D = 3g/liter, E = 4 g/liter, and F = 5 g/liter. The results showed that the KNO3 concentration treatment had an effect on increasing the growth and yield of potted chrysanthemum plants. Treatment with KNO3 concentration of 4 g/liter (E) and KNO3 concentration of 5 g/liter (F) had a better effect than other treatments on the growth and yield of potted chrysanthemum Cyra Agrohorti varieties